Analysis of Nitroso-Proteomes in Normotensive and Severe Preeclamptic Human Placentas - Zhang, Hong-hai (Society for the Study of Reproduction, Inc., 2011)
Nitric oxide (NO) plays a key role in placental biology, and placental dysfunction is the main pathogenesis pathway for preeclampsia, yet the direct placental targets of NO actions have not been determined. Covalent adduction of an NO moiety to cysteines, termed S-nitrosylation (SNO), is emerging as a key route by which NO can directly modulate protein functions. This study was conducted to analyze global S-nitroso (SNO)-proteins in human placentas and to determine if their levels differ in normotensive versus severe preeclamptic placentas. Although total nitrite/nitrate increased, total levels of SNO-proteins and nitrosylated forms of endothelial NO synthase and heat shock protein 90 were decreased by preeclampsia. We further compared normotensive and preeclamptic placental nitroso-proteomes (total SNO-protein profiles) by using a biotin and CyDye switch test combined with two-dimensional fluorescence difference gel electrophoresis (2D-DIGE) and identified SNO-proteins by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry. Numerous SNO-proteins were displayed as spots on 2D-DIGE gels. One hundred spots of interest were excised; 46 spots were identified, of which 8 spots were novel SNO-proteins; levels of 15 spots were increased, and 6 spots were decreased, and the rest were unchanged by preeclampsia. Pathway analysis suggested that placental SNO-proteins are involved in regulating various cellular functions including protein synthesis, cell movement and metabolism, cell signaling, and other functions. These data therefore show for the first time that SNO is a crucial mechanism by which NO directly regulates placental proteins linked to various biological pathways. The significantly altered placental nitroso-proteome in preeclampsia suggests that SNO plays a role in the placental pathophysiology in preeclampsia.